Restlessness with Manic Episodes due to Right Parietal Infarction - Kang, Suk Yun (The Korean Movement Disorder Society, 2010)
Mood disorders following acute stroke are relatively common. However, restlessness with manic episodes has rarely been reported. Lesions responsible for post-stroke mania can be located in the thalamus, caudate nucleus, and temporal and frontal lobes. We present a patient who exhibited restlessness with manic episodes after an acute infarction in the right parietal lobe, and summarize the case reports involving post-stroke mania. The right parietal stroke causing mania in our case is a novel observation that may help us to understand the mechanisms underlying restlessness with mania following acute stroke.